2019
DOI: 10.1109/tia.2018.2867330
|View full text |Cite
|
Sign up to set email alerts
|

Power Quality Assessment in Shipboard Microgrids Under Unbalanced and Harmonic AC Bus Voltage

Abstract: Abstract-Power quality (PQ) is becoming more and more critical issue in shipboard microgrid systems (SMG). Especially, the impact of voltage unbalance combined with harmonic distortions on the SMG behavior has not been fully investigated. In this paper, simple power quality assessment models and a series of controlled experiments are proposed and carried out in a real ship under seagoing conditions. The ship experimental results are presented and discussed considering non-linear bow thruster load and high powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 29 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…In addition, it can also result in other undesirable consequences, such as thermal aging of insulation, overheated bearings and reduced efficiency of equipment operation. An experimental study [37] where a single phase of a 3-ph heating load was disconnected to emulate an unbalanced load concluded that the harmonic distortion phenomenon during both steady state and transient operation phenomenon is more significant when voltage imbalance is present in the system. In the aforementioned experiment, the voltage THDs were in the range of 6.52%-6.73%, whereas for the unbalanced condition (imbalance factor u2=1.76%), the range of the THD changed to 6.15-7.38% depending on the line-to-line voltage [37].…”
Section: A Voltage Variations and Imbalancementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can also result in other undesirable consequences, such as thermal aging of insulation, overheated bearings and reduced efficiency of equipment operation. An experimental study [37] where a single phase of a 3-ph heating load was disconnected to emulate an unbalanced load concluded that the harmonic distortion phenomenon during both steady state and transient operation phenomenon is more significant when voltage imbalance is present in the system. In the aforementioned experiment, the voltage THDs were in the range of 6.52%-6.73%, whereas for the unbalanced condition (imbalance factor u2=1.76%), the range of the THD changed to 6.15-7.38% depending on the line-to-line voltage [37].…”
Section: A Voltage Variations and Imbalancementioning
confidence: 99%
“…An experimental study [37] where a single phase of a 3-ph heating load was disconnected to emulate an unbalanced load concluded that the harmonic distortion phenomenon during both steady state and transient operation phenomenon is more significant when voltage imbalance is present in the system. In the aforementioned experiment, the voltage THDs were in the range of 6.52%-6.73%, whereas for the unbalanced condition (imbalance factor u2=1.76%), the range of the THD changed to 6.15-7.38% depending on the line-to-line voltage [37]. In more severe cases, faults occurring in certain portions of shipboard power systems can also bring about voltage dips or spikes [25].…”
Section: A Voltage Variations and Imbalancementioning
confidence: 99%
“…A N increasing number of applications of AC-distributed power systems have been made possible due to advances in semiconductor technologies and inverter topologies. These applications can be found in several new and emerging fields, including renewable energy generation [1], hybrid and electric vehicles [2], smart grids [3], electric aircrafts [4], and electric ships [5].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency fluctuations can also lead to undesirable resonances and cause crucial equipment such as measuring instruments to malfunction, while the effects of poor voltage profile include problems such as lamp flicker. A worst case scenario of partial or total blackout of the power network endangering the safety of man and machine onboard can also result from these power quality issues (Xu et al, 2006;Prousalidis et al, 2007;Prousalidis et al, 2009;Jayasinghe et al, 2018;Liu et al, 2019). The problem of instantaneous frequency modulation is recognized by some ship classification societies such as Lloyd Register of shipping which stipulates limits on "a maximum rate of change of frequency not exceeding ±1.5 Hz per second during cyclic frequency fluctuations" (Lloyd's Register, 2019).…”
Section: Introductionmentioning
confidence: 99%